Thalidomide in the Treatment of Sweet's Syndrome and Eosinophilic Folliculitis Associated With Immune Reconstitution Inflammatory Syndrome - Dong, Rong-Jing; Huang, Shi-Zhen; Upadhyay, Pratishtha; Shrestha, Samip; Zhai, Ya-Jie; Li, Yu-Ye (Frontiers in Medicine, 2020)
Sweet’s syndrome and eosinophilic folliculitis are aseptic inflammatory dermatitis mainly because of infiltrated neutrophils and eosinophils on skin respectively. These diseases rarely overlap or coexist in the same patient, especially co-occur in HIV infected patient. Here, we report a rare case of an AIDS patient who developed eosinophilic folliculitis and Sweet’s syndrome within 1 month of initial antiretroviral therapy, presumably due to immune reconstitution inflammatory syndrome. The CD4+ T cell counts increased dramatically from 70 cells/μL to 249 cells/μL within a period of 1 month. Interestingly, the patient was rapidly and strikingly responsive to thalidomide, which has anti-inflammatory, immune regulation, inhibition of neutrophil chemotaxis etc. Moreover, we focused our attention on discussing the clinical, pathological and possible pathogenic aspects of the rare overlap of HIV complicated with neutrophilic and eosinophilic dermatosis.